Enhancing Students Historical Thinking Based on Augmented Reality (AR) Media in Social Studies - Siti Logayah, Dina; Salira, A Budhi; Rakhman, Muhammad Arief; Darmawan, Rizal Akbar; Heryanto, Fahmi Nugraha (International Journal of Social Learning (IJSL), 2025)
This study aims to analyze the effectiveness of the use of Augmented Reality (AR) technology in improving students' historical thinking skills, class VII at SMPN 13 Bandung in learning Social Studies. The quantitative approach with the Design Based Research (DBR) research method includes four stages, namely analysis, design, implementation, and evaluation. Data collection through observation, interviews, and questionnaires, then data analysis techniques are carried out descriptively. The results of the study showed that the effectiveness of using AR can increase student learning interactions by 82%, meaning that it shows more active involvement than conventional learning. Conceptual understanding increased by 45%, while critical thinking skills increased by 40%. This means that 85% of students are better able to understand the material on the development of Indonesian society during the Hindu and Buddhist periods in social studies. Other findings are that 90% based on information from social studies teachers there was an increase in students' analytical abilities and 95% of students expressed a high interest in using AR in social studies. This finding has an impact that the use of AR technology can improve students' historical thinking skills.